2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090881
|View full text |Cite
|
Sign up to set email alerts
|

SN-38:β-cyclodextrin inclusion complex for in situ solidifying injectable polymer implants

Abstract: One of the most useful techniques to treat cancer is chemotherapy. However, anticancer drugs, such as SN-38, have limited solubility with strong side effects. This work aims to use SN-38:β-cyclodextrin (β-CD) inclusion complex for an injectable polymeric in situ forming implant containing poly(ethylene glycol) (PEG), poly(ε-caprolactone), and poly(D, L-lactide). It was found that implant formation and SN-38 encapsulation efficiency directly depended on weight ratio of SN-38 and β-CD. At the ratio of SN-38:β-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Inherent poor water solubility and stability pose a great challenge to develop an optimal formulation of SN38 [8][9][10][11], consequently, several prodrugs, polymer conjugates [3,11,12], micelles [13][14][15][16][17][18], liposomes [19][20][21] and nanoparticles [8][9][10]22], polymeric implants [23] and cells as drug carriers [24] were investigated to improve its biopharmaceutical properties [12][13][14][15][16][17][18][19][20][21][22]25,26]. Broadly, these strategies may be divided into two categories: chemical derivatization of SN38; and encapsulation into a carrier system.…”
Section: Introductionmentioning
confidence: 99%
“…Inherent poor water solubility and stability pose a great challenge to develop an optimal formulation of SN38 [8][9][10][11], consequently, several prodrugs, polymer conjugates [3,11,12], micelles [13][14][15][16][17][18], liposomes [19][20][21] and nanoparticles [8][9][10]22], polymeric implants [23] and cells as drug carriers [24] were investigated to improve its biopharmaceutical properties [12][13][14][15][16][17][18][19][20][21][22]25,26]. Broadly, these strategies may be divided into two categories: chemical derivatization of SN38; and encapsulation into a carrier system.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins have been shown to increase the cytotoxicity of several antineoplastic drugs like camptothecin (16,17), curcumin (18), doxorubicin, docetaxel (19), paclitaxel (20), etc. SN-38-βCD complex has been used to prepare in situ polymeric implants (21), but there was no detailed study reported on the effect of CDs on improving solubility, stability, and cytotoxicity of SN-38. In this study, we investigated the effects of four different types of modified β-cyclodextrins, namely, sodium sulfobutylether β-cyclodextrin (SBEβCD), hydroxypropyl β-cyclodextrin (HPβCD), randomly methylated β-cyclodextrin (RMβCD), and methylated β-cyclodextrin (MβCD) on the solubility, stability, and cytotoxicity of SN-38.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit the full therapeutic potential of SN-38, a variety of drug delivery systems have been extensively investigated, including polymeric implants, 11 micelles, [12][13][14] liposomes, 15,16 polymer conjugates, 7,17 and nanoparticles. 9,18 Unfortunately, although these techniques enhanced the solubility of SN-38, there are also many inherent drawbacks, such as low encapsulation efficiency and low drug loading, 10,15 poor stability during conjugation process, and low final yield of polymer conjugates.…”
Section: Introductionmentioning
confidence: 99%